A life crossing borders : memoir of a Mexican-American Confederate - Tafolla, Santiago, 1837-1911 (Recovering the U.S. Hispanic Literary Heritage Project publication., 2010)
In the memoir he began in 1908, Santiago Tafolla recalls finding himself--along with his fellow Mexican Confederate soldiers--terrorized by white Confederates. When the americanos take up arms and threaten to eliminate all the "greasers," Tafolla is forced to desert in order to survive. Born in Santa Fe in 1837, nine years before Mexico lost control of the region following the Mexican-American War, Tafolla chronicles his life during turbulent times. He experienced firsthand the racism prevalent to the time period and was an eyewitness to slavery. He was a veteran of the Texas Indian. Wars and the U.S. Civil War, having served as a bugler for both the northern and southern armies. And he spent the last 35 years of his life as a methodist circuit-riding preacher when most Hispanics were Catholics. The preservation and publication of this memoir is almost as fascinating as the life described within its pages. Edited by Santiago's great-grand-daughters, Carmen Tafolla and Laura Tafolla, it includes sample pages from the original, handwritten manuscript; a transcription of the complete original Spanish memoir; an epilogue describing the significance of his later life; the English translation; and historical photos. Published as part of the Recovering the U.S. Hispanic Literary Heritage Project series, A Life Crossing Borders is an invaluable aid to understanding the upheavals of the nineteenth century in North America. In recovering Santiago Tafolla's memoir, scholars and great-granddaughters Carmen and Laura have contributed a remarkable work of inestimable historical and literary value, Tafolla's rich and nuanced memoir details a young Hispano's life in the vortex of U. S. wars of Western expansionism and in the Civil War. Tafolla, who crosses limits and boundaries of language, religion and political allegiance, is a critically important nineteenth century voice. His memoir significantly adds to our knowledge and understanding of Latina/o history and literature; it is a must for every library!--Antonia Castarieda, Ph.D., Independent Scholar --Book Jacket.